Pengembangan Bahan Ajar Berbantuan Video Pembelajaran Materi Dari Aku Untuk Indonesia Kelas V SD Negeri 26 Pontianak Tenggara - Ratu Balqis; Siti Halidjah; Asmayani Salimi (Journal on Education, 2024)
This study aims to determine the feasibility of teaching material products assisted by learning videos of material from me for Indonesia. The method used in this research is the ADDIE method. The results of this study indicate that the media expert received an assessment with an average of 4.81 with “very feasible” criteria, the material expert received an assessment with an average of 4.79 with “very feasible” criteria, the results of the small group student response assessment obtained a score of 77% with “good” criteria, and the results of the assessment of 21 students in the large group trial 81% with “very good” criteria. This means that overall teaching materials assisted by learning videos have “very feasible” criteria for use in grade V elementary schools. Thus it can be concluded that the use of teaching materials assisted by learning videos is indeed very attractive to students to develop interest in learning and so that they are not easily bored in participating in learning if they only use the ceraah method.